International political organisations - "Singh, K .P." (New Delhi, 2008)
This book contains adequate cognizance about six Political Institutions of the world and their contemporary steps taken in the construction of new globe. UNO, EU, NAM, ASEAN, SAARC, IBSA are the six most important institutions which have their own role to play in today's multipolar world. UNO has been the prominent platform for International Politics. NAM too has been active in post British liberalization period. EU, ASEAN, SAARC, IBSA are regional as far as their nature and functioning is conserned but they are actively participating on International Platform too. This book is equipped with the knowledge to understand the historical background of these institutions and the role being played by them in the development work of 21st century. It contains the relevant programs being funded/run by these six important most organizations of the world. The book covers almost all the details pertaining to the recent summits of these International Organisations besides their treasurable decisions.
Keywords: International Organisations